Revolt of the Tar Heels : the North Carolina populist movement, 1890-1901 - Beeby, James M., 1969- (University Press of Mississippi, 2008)
During the 1890s, North Carolina witnessed a political revolution as the newly formed Populist Party joined with the Republicans to throw out do-nothing, conservative Democrats. Focusing on political transformation, electoral reform, and new economic policies to aid poor and struggling farmers, the Populists and their coalition partners took power at all levels in the only southern state where Populists gained statewide office. For a brief four years, the Populists and Republicans gave an object lesson in progressive politics in which whites and African Americans worked together for the better.